Charlie Quinn lets go : a novel - Varon, Jamie (Park Row Books, 2025)
"Charlie Quinn has spent her life playing by the rules. But when,on her thirtieth birthday, she is laid off, her boyfriend leaves her because their life is too "predictable" and she spends the night with violent food poisoning, she hits rock bottom at a stunning velocity, and her carefully constructed world unravels. She has no choicebut to return to her childhood home in LA, where her little sister strikes up an idea: Can control freak Charlie go a whole month saying yes to anything her free-spirited sister requests? Charlie agrees,if only to prove that living by one's whims will result in nothing but disaster and disappointment. But when a serendipitous encounter with her high school crush leads to a month of steamy no-strings romance, Charlie starts questioning her monotonous existence. Can she learn to loosen her grip, to let go of past heartbreak, to finally say yes to a messy, bold and exciting life?"--Provided by publisher.